2003
DOI: 10.1590/s0100-67622003000600003
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrientes no sistema solo-Pinus caribaea Morelet em plantios apresentando amarelecimento das acículas e morte de plantas

Abstract: Com o objetivo de contribuir no diagnóstico de causas que têm levado à morte precoce de pinheiros, verificada após amarelecimento e necrose progressiva das acículas, foi desenvolvido este estudo em áreas de cerrado, no oeste de Minas Gerais. Foram comparadas árvores de Pinus caribaea Morelet das variedades caribaea e hondurensis, plantadas entre 1977-82. Em cada local de amostragem coletou-se material de 20 árvores, sendo 10 com acículas amarelecidas e 10 normais. Foram coletados acículas e tecidos do xilema e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 6 publications
1
6
0
6
Order By: Relevance
“…A liberação de ácidos orgânicos, por acículas em decomposição, e a maior absorção de cátions do que de ânions são possíveis causas da acidifi cação dos solos sob pínus (Giddens et al, 1997). Ademais, em plantios desta espécie fl orestal, o acúmulo de acículas na superfície do solo promove a retenção de quantidades consideráveis de nutrientes na serapilheira, o que altera o equilíbrio do sistema solo-planta (Chaves & Corrêa, 2005). Assim como sob carvoeiro, no presente trabalho, decréscimos no pH do solo e nos teores de bases também foram relatados em áreas cultivadas com outras leguminosas arbóreas, como Albizia (Rhoades & Binkley, 1996) e Acacia mangium (Yamashita et al, 2008), em comparação a áreas dominadas por espécies não leguminosas.…”
Section: Resultsunclassified
“…A liberação de ácidos orgânicos, por acículas em decomposição, e a maior absorção de cátions do que de ânions são possíveis causas da acidifi cação dos solos sob pínus (Giddens et al, 1997). Ademais, em plantios desta espécie fl orestal, o acúmulo de acículas na superfície do solo promove a retenção de quantidades consideráveis de nutrientes na serapilheira, o que altera o equilíbrio do sistema solo-planta (Chaves & Corrêa, 2005). Assim como sob carvoeiro, no presente trabalho, decréscimos no pH do solo e nos teores de bases também foram relatados em áreas cultivadas com outras leguminosas arbóreas, como Albizia (Rhoades & Binkley, 1996) e Acacia mangium (Yamashita et al, 2008), em comparação a áreas dominadas por espécies não leguminosas.…”
Section: Resultsunclassified
“…This distribution is related to the introduction of different species, coming from a wide variation in ecological conditions in their original dispersion. This fact provided a high genetic variability and, as a consequence, a greater adaptation to various climate and soil conditions (CHAVES & CORRÊA, 2005, SHIMIZU, 2006 the wide use of the genus can be attributed to the technological characteristics of its wood, which allows different applications, including construction, sawmill industry, laminated products, plates, energy, paper, and cellulose. Pinus caribaea is among the pine species most cultivated in the country.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, the negative effects of inadequate soil management in Brazilian areas of forest plantations have been investigated and highlighted (CHAVES;CORREA, 2005;LILIENFEIN et al, 2000;ZÖTTL, 1987) As reported in more recent trials, significant increases in productivity due to lime and fertiliser applications have been observed in coniferous forests (FERREIRA et al, 2001). However, according to Brito et al (1986) Pinus caribeae forests planted in soils treated with liming and macronutrients showed increasing growth-ring mass production up to the third year; but opposite results were obtained with older trees.…”
Section: Introductionmentioning
confidence: 99%